Collective Responsibility for Severe Poverty. Issue 4 (13th May 2020) - Brooks, Thom
Abstract: Thomas Pogge has argued powerfully for the view that states which are responsible for severe poverty collectively share this responsibility. I claim that this rough equality of collective responsibility is not compelling. Relevant states may share collective responsibility for severe poverty, but some states possess much more responsibility than others. It may prove difficulty determining precisely how much more or less responsible some states are than others. Nonetheless, Pogge's account should be revised to recognize more clearly the inequality of contribution that relevant states have towards collective responsibility for severe poverty. Abstract : Even if we accept Pogge's background argument that relevant states share collective responsibility for severe poverty, we should reject the view that these states share roughly equal collective responsibility – in fact, this can vary considerably.